2011
DOI: 10.1017/s0007114511000407
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6: a challenging link between nutrition and inflammation in CVD

Abstract: The objective of the present review is to highlight the relationship between low vitamin B 6 status and CVD through its link with inflammation. While overt vitamin B 6 deficiency is uncommon in clinical practice, increasing evidence suggests that marginal vitamin B 6 deficiency is rather frequent in a consistent proportion of the population and is related to an increased risk of inflammation-related diseases. Ample evidence substantiates the theory of atherosclerosis as an inflammatory disease, and low plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 94 publications
(209 reference statements)
5
57
1
Order By: Relevance
“…Epidemiological studies have shown that, while overt deficiency is rare, the prevalence of moderate vitamin B 6 deficiency in the general population is more pronounced, ranging from approximately 18% in North America and reaching up to 50% in Europe [25,34]. Marginal B 6 deficiency has been linked to the development of chronic inflammation in rheumatoid arthritis, colorectal cancer and cardiovascular diseases [35,36]. Additionally, several factors including the consumption of B 6 antagonists may further perturb the biochemical availability of endogenous PLP [11].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that, while overt deficiency is rare, the prevalence of moderate vitamin B 6 deficiency in the general population is more pronounced, ranging from approximately 18% in North America and reaching up to 50% in Europe [25,34]. Marginal B 6 deficiency has been linked to the development of chronic inflammation in rheumatoid arthritis, colorectal cancer and cardiovascular diseases [35,36]. Additionally, several factors including the consumption of B 6 antagonists may further perturb the biochemical availability of endogenous PLP [11].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative causes for the relationship between low ALT and mortality could include associations of low ALT with pyridoxine deficiency [9,42], low levels of sex hormones [32,43], higher Nterminal pro-Brain natriuretic peptide (BNP, secreted by ventricular myocytes in response to…”
mentioning
confidence: 99%
“…Furthermore, bioavailability of intracellular folate, vitamin B12 and vitamin B2 modulates the concentration of p-tHcy. It has been reported that 5-PLP acts as an antioxidant, and decreased concentrations of 5-PLP may be associated with inflammation and CVD [47][48][49] . A decrease in the concentration of plasma 5-PLP in individuals who consumed vitamins E + C may suggest that an interaction between 5-PLP and vitamins E + C may have caused increased secretion or utilization of 5-PLP in the elderly on strength training.…”
Section: Discussionmentioning
confidence: 99%